Helianthemum pugae (Cistaceae), a new species from central Mexico - Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1995)
Helianthemum pugae Calderón, sp. nov., is based on collections made in northern Guanajuato and southwestern San Luis Potosí. It is similar to H. patens Hemsl. Species of wider distribution in central Mexico, which was found to grow sympatrically with H. pugae.